2x - y = -4
-3x + y = -9
From the first equation:
y = 2x + 4
Substitute this into the second equation:
-3x + 2x + 4 = -9
-x + 4 = -9
-x = -13
x = 13
Then plug this answer back into the first equation
2*13 - y = -4
26 - y = -4
-y = -30
y = 30
algebra - i need help with these problems (either a solution or how to plug them...
Substitution Method-Plz help - Use the Substitution method to solve the system ...
math substitution method - use the substitution method to solve 7x+5y=-26 x=28-...
algebra - how do you use the substitution method to solve x + y =2 y = -2x
math - solve each system of equations by substitution. y=3x-9 please help ...
algebra - Use the method of substitution to solve the system. xy=1 4x-y+3=0
Algebra - y=4x-1 y=2x-5 Use substitution to solve each system of equations
algebra - Use the substitution method to solve the linear system. Thanks! s= t+4...
Algebra - Use the substitution method to solve -x + 3y=24 5x +8y=-5
algebra - How do i use substitution to solve each system? y= 0.8x + 7.2 20x + ...